Stability of heterogeneous linear and nonlinear car-following models - Matthias Ehrhardt; Antoine Tordeux (Franklin Open)
Stop-and-go waves in congested road traffic are complex collective phenomena with significant implications for traffic engineering, road safety and the environment. Despite decades of research, understanding and controlling these oscillatory dynamics remains challenging. This article examines two classes of heterogeneous car-following models with quenched disorder to shed light on the underlying mechanisms that drive traffic instability and stop-and-go dynamics. Specifically, a scaled heterogeneity model and an additive heterogeneity model are investigated, each of which affects the stability of linear and nonlinear car-following models differently. We derive general linear stability conditions that we apply to specific models and illustrate by simulation. The study provides insight into the role of individual heterogeneity in vehicle behaviour and its influence on traffic stability.